2016
DOI: 10.1136/bjophthalmol-2015-307730
|View full text |Cite
|
Sign up to set email alerts
|

Neuroretinal rim in non-glaucomatous large optic nerve heads: a comparison of confocal scanning laser tomography and spectral domain optical coherence tomography

Abstract: In large optic discs, BMO-MRW is thinner compared with normal-sized discs and correlates better than CSLT parameters with the RNFLT. An age-depended loss of BMO-MRW needs to be taken into account in evaluation of the neuroretinal rim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 26 publications
1
37
0
2
Order By: Relevance
“…Both parameters are similar to the 246 normative eyes with regular disc size (mean BMO area, 1.74 mm 2 ; BMO-MRW range, 300–380 μm) 12. In non-glaucomatous large optic discs, BMO-MRW and RNFLT are thinner 22. Patients with regular visual field function and OHT did not show a significant decrease of BMO-MRW or RNFLT compared with normal controls.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Both parameters are similar to the 246 normative eyes with regular disc size (mean BMO area, 1.74 mm 2 ; BMO-MRW range, 300–380 μm) 12. In non-glaucomatous large optic discs, BMO-MRW and RNFLT are thinner 22. Patients with regular visual field function and OHT did not show a significant decrease of BMO-MRW or RNFLT compared with normal controls.…”
Section: Discussionsupporting
confidence: 69%
“…Special situations of the ONH are yet to address, for example, very small or very large discs, myopic discs, tilting of the disc as well as other papillary anomalies. This workgroup has recently published reference data on 102 controls in SD-OCT analysis of the ONH in non-glaucomatous large optic discs 22. Malik et al 30 recently published an analysis on the diagnostic power in myopic discs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, patients with an additional regular ACP showed no loss at all. Several studies could demonstrate an age-related loss of RNFL thickness in Bruch's membrane opening (BMO)-based optical tomography of the ONH [22][23][24] . Chauhan et al [22] showed an average age-related annual RNFL loss of -0.21 μm in 246 normalsized optic discs of healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…1,[4][5][6][7][8][9][10][11] Correlation of morphometric parameters of the ONH and visual field function has been evaluated in several studies. 1,[12][13][14][15][16][17][18][19][20][21][22] In addition to the clinically available parameters Bruch's membrane opening-based minimal rim width (BMO-MRW) and peripapillary retinal nerve fiber layer (RNFL) thickness, two studies on the two dimensional parameter Bruch's membrane opening minimal rim area (BMO-MRA) showed high diagnostic power for all ONH sizes and equalized differences in BMO-MRW between very large and very small ONHs. 1,23 As follow-up data become available, first studies were conducted to assess the performance of SD-OCT for detection of progression of glaucomatous damage to the ONH.…”
mentioning
confidence: 99%